Culturally Responsive Teaching (CRT) and Awareness of Own Culture: A Predictive Model for Enhancing STEM Education - Akinbobola, Akinyemi; Bada, Abiodun; Adewumi, Abayomi (Universitas Negeri Semarang, 2025)
We investigated the predictive role of culturally responsive teaching (CRT) and awareness of own culture (AOC) in improving STEM education. The researchers leveraged on the importance of CRT by exploring its direct and mediated effects on knowledge of student’s culture (KSC), and patterns of cultural interaction (PCI), among STEM teachers in Southwest, Nigeria. Employing a survey research approach, 343 secondary school STEM teachers were involved. Eight hypotheses were tested for acceptance or otherwise with Smart PLS-4. Findings from the study revealed that the nuances of awareness of own culture have both direct and mediated significance on knowledge of student culture and patterns of cultural integration. The findings also reveal a direct, positive and significant impact of CRT on knowledge on students’ culture and patterns of cultural integration. The study concludes that these nuances of awareness of culture can have a significant impact on the development of STEM education.